Scale of perceived exertion as injury prevention tool for young football players - A. V. Borisova; F. V. Takhavieva; M. M. Kuznetsova; I. S. Dolgalev; Y. I. Preobrazhensky; Z. O. Shabanova; E. A. Malyakina; M. S. Butovsky (Спортивная медицина: наука и практика)
Objective: evaluation of the feasibility of using the Borg CR10 perceived exertion scale in the training process of young football players and its role in injury prevention.Material and methods: 48 athletes aged 15–17 were examined by scale of perceived exertion during the 7 month every day within 20 minutes after the training. The coaches also assessed the degree of perceived exertion. A comparative retrospective analysis of injuries was done for the periods of the mycrocycle of the youth football league of the seasons 2020–2021 and 2021–2022 based on muscle injuries, ligament and joint capsular injuries.Results: Athletes’ scores on the Borg CR10 scale in the preparation, competition and transitional stages of the competitive macrocycle are 5.08 ± 1.28, 5.00 ± 1.16 and 4.67 ± 1.38, respectively. The coaches’ scores for the aforementioned periods are 4.78 ± 0.89, 5.09 ± 1.05 and 4.82 ± 0.99. The total scores of players and coaches is 5.20 ± 1.85 and 4.96 ± 1 respectively. Moreover, there is no statistically significant difference between the rate of perceived exertion between players and coaches for the whole season (p = 0.288).There is a decreased injury rate in young professional athletes group when the Borg CR10 scale of perceived exertion is measured in a season with the use of this scale compared to a season where the Borg CR 10 scale was not used (p = 0,028).Conclusion: the Borg СR10 scale is a useful methodology for assessing the level of perceived exertion of a young athlete and can be used for early training corrections in order to reduce injuries.